PENGARUH TEKNIK GENGGAM JARI (Finger Hold) TERHADAP PENURUNAN INTENSITAS NYERI OPERASI POST SC (Sectio Caesarea) DI RSU SEMBIRING TAHUN 2024” - manik, maria hermita; rosaulina, meta (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Since SC is only performed when a delivery trial has failed, the fetus must be born through an incision on both the uterine and abdominal walls. This puts the fetus and the mother at risk. The pain caused by SC is at the incision site, it can be pelvic pain— acute pain. Hence it should also be addressed immediately as it will lead to more complications if not acted upon in time. Instead of medication, physiotherapy involves use of hand held tools in curbing health issues affecting one's physical, psychological, cognitive well-being and needs individuals with physical disabilities would require for socialization. The autonomic nervous system, which regulates automatic bodily activities including blood flow, is stimulated by pressing certain areas as part of this therapy & interfere with transmission of pain signals along with inducing psychological effects aimed at reducing pain experienced during SC. The study seeks to eval_uate the impact of finger-hold technique in reducing the intensity of post-SC pain. This research was undertaken at Sembiring General Hospital in April-May 2024.”